Hybrid screw fixation for femoral neck fractures: Does it prevent mechanical failure?. Issue 8 (August 2022) - Cuellar, Derly O.; Garcia Velez, Dencel A.; Bledsoe, Gary; Tracy Watson, J.
Highlights: Specimens underwent standardized femoral neck osteotomies, with 5 mm posteromedial wedge removed to simulate comminution. Group 1 utilized one fully threaded calcar screw & two partially threaded superior screws. Group 2 utilized all partially threaded screws. All specimens loaded to 10, 000 cycles and then to failure. Group 1 configuration resulted in significantly stronger constructs, with higher axial load and increased cycles prior to failure. Abstract: Introduction: Traditionally, femoral neck fracture fixation has been performed using three partially threaded cancellous screws. However, fracture collapse with femoral neck shortening, and varus deformation frequently occurs due to posterior medial comminution and lack of calcar support. We hypothesize replacing the inferior neck/calcar screw with a fully threaded, length stable, screw will provide improved biomechanical stability, decrease femoral neck shortening and varus collapse. Methods: Ten matched cadaveric pairs (20 femurs) were randomly assigned to two screw fixation groups. Group 1 (Hybrid) utilized one fully threaded calcar screw & two partially threaded superior screws. Group 2 (PT) utilized all partially threaded screws. Specimens underwent standardized femoral neck osteotomies, 45° from the horizontal, with 5 mm posteromedial wedge removed to simulate posteromedial comminution. Screws were placed using fluoroscopic guidance. Specimens were biomechanically tested using two loading sequences: 1) Axial load applied up to 700 N, followed by cyclic loading at 2 Hz with loads of 700 to 1, 400 N for 10, 000 cycles. 2) All surviving constructs were cyclically loaded to failure in stepwise incremental manner with max load of 4, 000 N. Paired t-tests used to compare stiffness, cycles to failure, and max load to failure (defined as 15 mm load actuator displacement). Results: Construct stiffness was 2848 ± 344 N/mm in PT vs. 2767 ± 665 for Hybrid ( P = 0.628). Load to failure demonstrated, hybrid superiority with max cycles to failure (3797 ± 400 cycles) vs. (2981 ± 856 cycles in PT) ( p = 0.010), and max load prior to failure (3290 ± 196 N) vs. (2891 ± 421 N in PT) ( p = 0.010). No significant difference in bone mineral density was noted in any of the specimens. Conclusions: Our study is the first to assess the biomechanical effects of hybrid fixation for femoral neck fractures. Hybrid screw configuration resulted in significantly stronger constructs, with higher axial load and increased cycles prior to failure. The advantageous mechanical properties demonstrated using a fully threaded inferior calcar screw provides a length stable construct which may prevent the common complication of excessive femoral neck shortening, varus collapse and poor functional outcome.